The Cardenolides of Thevetia Peruviana Grown in Malaysia - IKRAM M SAID; ZARINA A RAHMAN (ASEAN Journal on Science and Technology for Development, 1986)
The cardiac glycosides found in the seed kernels of Thevetia peruviana grown in Malaysia was investigated. Thevetin, a triglycoside, was separated into thevetin A and thevetin B by DCCC while the monoglycoasides obtained after incubation of the seeds were identified as nerlifolin, neriifolin monoacetate, and peruvoside.